TRPM7 in cerebral ischemia and potential target for drug development in stroke - Bae Christine You-jin; Sun Hong-shuo (Acta Pharmacologica Sinica, 2016)
Searching for effective pharmacological agents for stroke treatment has largely been unsuccessful. Despite initial excitement, antagonists for glutamate receptors, the most studied receptor channels in ischemic stroke, have shown insufficient neuroprotective effects in clinical trials. Outside the traditional glutamate-mediated excitotoxicity, recent evidence suggests few non-glutamate mechanisms, which may also cause ionic imbalance and cell death in cerebral ischemia. Transient receptor potential melastatin 7 (TRPM7) is a Ca2+ permeable, non-selective cation channel that has recently gained attention as a potential cation influx pathway involved in ischemic events. Compelling new evidence from an in vivo study demonstrated that suppression of TRPM7 channels in adult rat brain in vivo using virally mediated gene silencing approach reduced delayed neuronal cell death and preserved neuronal functions in global cerebral ischemia. In this review, we will discuss the current understanding of the role of TRPM7 channels in physiology and pathophysiology as well as its therapeutic potential in stroke.